Students’ Integrated Science Process Skills Through CLIS Model - Emi Sulistri (STKIP Singkawang, 2019)
This research was conducted for improve students' integrated science process skills such as aspects of interpreting data, formulating hypotheses, planning experiments, and applying concepts through the CLIS learning model. This quantitative research with pre-experimental design uses the one group pre-test post-test design research design. The subjects in this study consisted of 27 students in one of the SMA Negeri on Singkawang City with the sampling technique in the form of a purposive sampling technique. The data collection technique in this study is tests of integrated science process skills that consists of 10 question multiple choice with five reasoned choices previously tested try with a reliability of 0.47 in the sufficient category. The increase in KPS analyzed by N-gain of 0.67 is in the medium category. It can be concluded that the application of CLIS learning model successfully enriching knowledges and can improve students’ integrated science process skills.